Global Supply Chain and Operations Management - Ivanov, Dmitry; Tsipoulanidis, Alexander; Schönberger, Jörn (Springer, 2019)
In everyday life, all of us take supply chain and operations management (SCOM) decisions. If you move to a new flat, location planning is first necessary. Second, you need a plan of how to design the overall process. This includes capacity planning, transportation planning, and human resource planning. You also need to replenish some items and do procurement planning. Finally, a detailed schedule for the day of the move is needed. Similarly, building a new house involves many SCOM decisions. Again, it starts with location selection. If you decide to coordinate the overall process by yourself, it is necessary to coordinate the entire supply chain of different manufacturers and workmen. In turn, they need the detailed data of your plans and forecasted data to plan their own process and sourcing activities. In order to avoid traffic jams at the building site, detailed coordination at the vehicle routing level is needed. SCOM belongs to the most exciting management areas. These functionalities are tangible and in high demand in all industries and services. This study book intends to provide both the introduction to and advanced knowledge in the SCOM field. Providing readers with a working knowledge of SCOM, this textbook can be used in core, special, and advanced classes. Therefore, the book is targeted at a broad range of students and professionals involved in SCOM. Special focus is directed at bridging theory and practice. Since managers use both quantitative and qualitative methods in making their decisions, the book follows these practical knowledge requirements. Decision-oriented and method-oriented perspectives determine the philosophy of the book. In addition, because of the extensive use of information technology and optimization techniques in SCOM, we pay particular attention to this aspect. Next, a strong global focus with more than 80 up-to-date cases and practical examples from all over the world is a distinguishing feature of this textbook. The case studies encompass different industries and services and consider examples of successful and failed SCOM practices in Europe, America, Asia, Africa, and Australia
A Decision-Oriented Introduction to the Creation of Value